Bringing some balance to fat bashing - Slavin, Joanne; Meijaard, Erik; Sheil, Douglas (Frontiers in Sustainable Food Systems, 2025)
Fats and oils are essential to human nutrition, yet often vilified in public discourse and dietary guidelines. We challenge the narrative that all dietary fats are inherently harmful and explore the vital roles fats play in health and food security. We review evidence on saturated, unsaturated, and trans fats, highlighting meta-analyses that question the links between saturated fat and health. We examine global disparities in fat access, shortcomings in current guidance, and the broader environmental and social impacts of fat sources. No crop is inherently good or bad, what matters is how, where, and by whom it is produced. We call for broad collaborations to produce more nuanced, evidence-based recommendations that reflect cultural traditions, sustainability, and the twin burdens of obesity and undernutrition.